Planificación Estratégica al Sindicato de Obreros Municipales de Loja (SOML), Periodo 2021-2026 - Agreda Quizhpe, Celina Daniela (2023)
This Curricular Integration Work named as “Strategic planning to Sindicato de Obreros Municipales de Loja (SOML), period 2021-2026”, was developed with the purpose to know the actual situation into the organization through of strategic planning which allows the organizational growth to take the best decisions. The methodology that was apply to achieve the objectives was done using the execution of two stages, the first was the actual situation diagnostic wich allowed to know the objectively reality and the development of the organization that is constitute with the internal and external factors analysis to stablish the to establish the strengths, opportunities, weaknesses and threats of the union and with the information obtained through the interview made to the general secretary, accountant and surveys applied to the union's members on relevant aspects of the union, the actual situation diagnostic was structured proposing development axes, training, promotion of organizational image and accountability to members, subsequently the second stage was done which is the elaboration of the strategic plan that was formulated with a mission and vision that identifies the association in the moment of elaborate the planning and formulation of strategic objectives, those were reflected in the programming matrix where are the strategics that provide for the administration of the organization, also the activities considered as important and specific actions to generate significant results and the indicators are proposed to measure the progress of the execution of activities in the future. To sum up, at the end of this investigation work, we have the diagnostic of the situation of the union, the developed axes, a mission, a vision and control and monitoring matrices, which will be used to evaluate the compliance of the strategic planning.